Effect of magnetic field and iron content on NMR proton relaxation of liver, spleen and brain tissues. (20th June 2014) - Hocq, Aline; Luhmer, Michel; Saussez, Sven; Louryan, Stéphane; Gillis, Pierre; Gossuin, Yves
<x xml:space="preserve">Abstract</x> Iron accumulation is observed in liver and spleen during hemochromatosis and important neurodegenerative diseases involve iron overload in brain. Storage of iron is ensured by ferritin, which contains a magnetic core. It causes a darkening on T2‐weighted MR images. This work aims at improving the understanding of the NMR relaxation of iron‐loaded human tissues, which is necessary to develop protocols of iron content measurements by MRI. Relaxation times measurements on brain, liver and spleen samples were realized at different magnetic fields. Iron content was determined by atomic emission spectroscopy. For all samples, the longitudinal relaxation rate (1/T1) of tissue protons decreases with the magnetic field up to 1 T, independently of iron content, while their transverse relaxation rate (1/T2) strongly increases with the field, either linearly or quadratically, or a combination thereof. The extent of the inter‐echo time dependence of 1/T2 also varies according to the sample. A combination of theoretical models is necessary to describe the relaxation of iron‐containing tissues. This can be due to the presence, inside tissues, of ferritin clusters of different sizes and densities. When considering all samples, a correlation (r2 = 0.6) between 1/T1 and iron concentration is observed at 7.0 T. In contrast the correlation between 1/T2 and iron content is poor, even at high field (r2 = 0.14 at 7.0 T). Our results show that MRI methods based on T1 or T2 measurements will easily detect an iron overloading at high magnetic field, but will not provide an accurate quantification of tissue iron content at low iron concentrations. Copyright © 2014 John Wiley & Sons, Ltd.